Cephalosporinases associated with outer membrane vesicles released by Bacteroides spp. protect gut pathogens and commensals against β-lactam antibiotics. (27th November 2014) - Stentz, Régis; Horn, Nikki; Cross, Kathryn; Salt, Louise; Brearley, Charles; Livermore, David M.; Carding, Simon R.
Abstract: Objectives: To identify β-lactamase genes in gut commensal Bacteroides species and to assess the impact of these enzymes, when carried by outer membrane vesicles (OMVs), in protecting enteric pathogens and commensals. Methods: A deletion mutant of the putative class A β-lactamase gene (locus tag BT_4507) found in the genome of the human commensal Bacteroides thetaiotaomicron was constructed and a phenotypic analysis performed . A phylogenetic tree was built from an alignment of nine Bacteroides cephalosporinase protein sequences, using the maximum likelihood method. The rate of cefotaxime degradation after incubation with OMVs produced by different Bacteroides species was quantified using a disc susceptibility test. The resistance of Salmonella Typhimurium and Bifidobacterium breve to cefotaxime in liquid culture in the presence of B. thetaiotaomicron OMVs was evaluated by measuring bacterial growth. Results: The B. thetaiotaomicron BT_4507 gene encodes a β-lactamase related to the CepA cephalosporinase of Bacteroides fragilis . OMVs produced by B. thetaiotaomicron and several other Bacteroides species, except Bacteroides ovatus, carried surface-associated β-lactamases that could degrade cefotaxime. β-Lactamase-harbouring OMVs from B. thetaiotaomicron protected Salmonella Typhimurium and B. breve from an otherwise lethal dose of cefotaxime. Conclusions: The production of membrane vesicles carrying surface-associated β-lactamases by Bacteroides species, which constitute a major part of the human colonic microbiota, may protect commensal bacteria and enteric pathogens, such as Salmonella Typhimurium, against β-lactam antibiotics.